Pengaruh Citra Merek Terhadap Loyalitas Pelanggan Teh Pucuk Harum Di Pondok Gede - Iwan Supriyanto; Vio Vie Tarisha; Widadatul Ngulya; Ahmad Rafiqi; Bagas Surya (Mathematics Education Study Program, 2025)
This research uses quantitative methods, with a non-probability sampling technique with a Purposive Sampling approach, the number of respondents is 100 people. Data collection techniques were carried out using observation and questionnaires. In calculating the multicollinearity test, it shows that the tolerance value is > 0.10 and the VIF value is 1,000, which means that multicollinearity does not occur. The calculation results of the t test where the sig value of the partial influence of X on Y is 0.000 < 0.05 and the t value is 4.167 > t table 1.666 (H1). So it can be concluded that brand image has a significant influence on the loyalty of customers of Puncak Fragrant in Pondok Gede, then. Therefore, from the results of these calculations, it is estimated that H0 is rejected and H1 is accepted, so it can be concluded that brand image has a significant effect on customer loyalty.